Neuropeptide Y in first-episode schizophrenia: is there any sex differences in the pathogeneses of schizophrenia? - Song, Jia-Qi; Xin, Wen; Yu, Jian-Jin; Zhao, Qing; Li, Hong-Na; Chen, Da-Chun (Frontiers in Psychiatry, 2024)
ObjectiveThis study investigated relationships between Neuropeptide Y levels and severity of psychiatric symptoms in first-episode schizophrenia patients, and explore the sexual heterogeneity in them.MethodsWe recruited 115 first-episode schizophrenia patients and 58 matched healthy controls, and measured serum Neuropeptide Y levels of them at baseline and again after 10 weeks of risperidone treatment in patient group. Patients were also evaluated with the Positive and Negative Symptoms Scale (PANSS) to reveal the severity of symptoms.Results95 patients completed the whole experiment. We find that mean Neuropeptide Y levels at baseline were significantly higher in patients than in controls (p<0.001), no matter in males or females. In males, there are positive correlations between Neuropeptide Y levels and PANSS scores at baseline (p<0.01), and between the change of them (p<0.05). However, we do not find these correlations in female patients. Furthermore, the interaction terms of NPY × sex were highly significant taking PANSS as dependent variable(p<0.001).ConclusionNeuropeptide Y plays a significant role in the pathogenesis of schizophrenia. In male patients, Neuropeptide Y is positively correlated with the severity of symptoms, while this correlation is not found in females. Continued efforts are needed to determine the sexual dimorphism in pathogeneses of schizophrenia.